Historical Documentary Material on the Role of the Catholic Church in Defending Indonesian Independence for High School Students - Prakoso, Eling Kris; Raharjo, Yoel Kurniawan; Printina, Brigida Intan (Indonesian Journal of History Education, 2023)
This study aims to develop a learning medium documentary film based on material on the Catholic Church's role in maintaining Indonesia's independence, which is suitable to be used by the XII grade senior high school students in history subjects specializing in basic competence 3.11 concerning responses to Indonesian independence. The research is the type of R&D (Research and Development) using the Borg & Gall model modified by Nana Syodih Sukmadinata. The product has been validated by two material experts, two media experts, and two film experts. Field trials were conducted through response interviews with one History teacher and two grade XII students. Data were collected using interviews, observation, and questionnaires with quantitative and qualitative data analysis techniques. The material expert validation results obtained a score of 4.6 with the "Very Good" criterion. The material expert validation two results obtained a score of 4.5 with the "Very Good" criterion. The validation results of Film Expert 1 obtained a score of 4.5 with the "Very Good" criterion. The validation results of Film Experts 2 obtained a score of 3.8 with the "Good" criteria. The validation results of Learning Media Experts 1 obtained a score of 4.7 with the "Very Good" criterion. The validation results of Learning Media Experts 1 obtained a score of 4.9 with the "Very Good" criterion. The results of interviews with teachers and students' responses concluded that the product was excellent and feasible to use.